An optimal GU-P2G-CCUS system operating model considering the carbon market and the cooperative game among participants - LI Yanbin; XU Yixuan; GE Rui; LI Yun; SUN Yanting; ZHANG Feng (Diance yu yibiao)
With the proposal of "dual carbon" goal, natural gas, as an important energy in the transition period of thermal power transformation, urgently needs to achieve safe and stable operation through green transformation. The application of carbon capture, utilization and storage (CCUS) technology will provide reliable technical support for the low-carbon development of gas power plants. This paper proposes a generator unit (GU) -power to gas (P2G)-CCUS system, and constructs a data-driven robust optimization (DDRO) model considering the uncertainty of wind power output. On this basis, because the existing optimization methods cannot achieve scientific cost allocation, considering the cooperative game relationship between the entities and the stability of the system operation, a cost allocation model based on the nucleolus based cooperative game (NCG) within the system is established to ensure the scientific and reasonable cost allocation. The results show that the introduction of CCUS can significantly reduce carbon emissions and gain additional profits by participating in the carbon market; DDRO model can effectively resist the interference of uncertain wind power output, enhance the security of system operation, and reduce the conservatism of traditional optimization model; NCG model can realize the reasonable allocation among GU, P2G and CCUS, so that each participant can obtain higher income than its independent operation, improving their willingness to cooperate, and thus enhancing the long-term and stability of cooperation.